HSP90 gene expression induced by aspirin is associated with damage remission in a chicken myocardial cell culture exposed to heat stress. Issue 4 (3rd July 2016) - Zhang, X.; Qian, Z.; Zhu, H.; Tang, S.; Wu, D.; Zhang, M.; Kemper, N.; Hartung, J.; Bao, E.
Abstract: To understand the potential protection of heat shock protein 90 (HSP90) induced by aspirin against heat stress damage in chicken myocardial cells, enzyme activities related to stress damage, cytopathological changes, the expression and distribution of HSP90, and HSP90 mRNA levels in the myocardial cells exposed to heat stress (42°C) for different durations with or without aspirin administration (1 mg/ml, 2 h prior) in vitro were investigated. Significant increase of enzyme levels in the supernatant of heat-stressed myocardial cells and cellular lesions characterised by acute degeneration, karyopyknosis and karyorrhexis were observed, compared to non-treated cells. However, the lesions of cells treated with aspirin were milder, characterised by earlier recovery of enzyme levels to the control levels and no obvious heat stress-related cellular necrosis. Stronger positive signals in the cytoplasm and longer retention of HSP90 signal in nuclei were observed in aspirin-treated myocardial cells than those of only heat-stressed cells. HSP90 level in the aspirin-treated myocardial cells was 11.1-fold higher than that in non-treated cells, and remained at a high level at the early stage of heat stress, whereas it was just 4.1-fold higher in only heat-stressed cells and returned rapidly to a low level. Overexpression of HSP90 mRNA in aspirin-treated cells was observed throughout the experiment, whereas HSP90 mRNA decreased significantly only in heat-stressed cells. The early higher HSP90 expression induced by aspirin during heat stress was accompanied by decreased heat stress damage, suggesting that aspirin might play an important role in preventing myocardial cells from heat stress damage in vitro .